A Study on the Implementation and Legal Protection of Electronic Land Registration in Gorontalo City - Nur Khairia Podungge, Lini Lisa; Yutye Imran, Suwitno; Taufiq Zulfikar Sarson, Mohamad (Estudiante Law Journal, 2025)
This study aims to examine and analyze the implementation of the electronic land registration system at the National Land Agency (BPN) Office of Gorontalo City, as well as the forms of legal protection provided to land rights holders in the event of errors in the system. This research adopts a normative-empirical legal approach, utilizing statutory, conceptual, and case study methods. Primary data were obtained from the Gorontalo City BPN Office, while secondary data were sourced from legislation, literature, and relevant research findings. All data were analyzed using a descriptive-qualitative method. The findings indicate that the implementation of the electronic land registration system in Gorontalo City has generally been in accordance with the applicable regulations, although it still faces various challenges from both the public and the internal operations of the BPN. The registration process continues to adhere to the fundamental principles and objectives of land registration. Legal protection for land rights holders is provided optimally through a correction mechanism in cases of errors in physical or juridical data, referring to the land register stored at the land office. Furthermore, the security features of electronic certificates are considered adequate, difficult to forge, and capable of preventing overlaps or duplication of certificates.